A hybrid routing approach for disaster management in manet - Soomro, Abdul Majid (2022)
Mobile Ad-Hoc Networks (MANET), known as dynamically reconfigurable networks, have no centralized control. MANET facilitates reliable communication between crew and fighters involved in uncertain situations and between central command crew and fighters. Routing is the search for a suitable route for communication, especially in disaster situations. MANET is the appropriate ad-hoc network to handle disaster situations due to its effectiveness and cost for the areas where fixed infrastructure was unavailable. There are many challenges in MANET related to the routing criteria of routing protocols. MANET suffered from two major issues when applied for data communication. The first drawback is a failure in the dynamic nature of nodes and instability, and the second is rapid change in the topology due to their mobility. The main reason behind the loss is a disaster that disturbs the normal execution of functionality. MANET still has route discovery issues because their communication between nodes is highly concerned. The cause behind this drawback is a route disconnection from source to destination, making the topology of nodes highly dynamic, especially in disaster management. Therefore, in this research, an improved hybrid approach (IHRP) that combines proactive and reactive routing protocols is suggested for these issues through quick network convergence in terms of speed and network density with the help of MANET services. The improved hybrid approach reduces route discovery and link breakage between highly mobilized nodes during disaster management. For this purpose, qualitative research methodology focuses on interpretation situations as well as the dedication to a case-based scenario is used in experiment 1 and experiment 2 that is related to the speed and network density in the research work towards helping the members of the community of practice (CoP) to utilize MANET services. The contrasting results between the IHRP and existing protocols indicate that the IHRP outperforms and increases from 9% to 12%.